KEWENANGAN KOMISI YUDISIAL DALAM PENGUSULAN PENGANGKATAN HAKIM AGUNG DIHUBUNGKAN DENGAN PASAL 71 UNDANG-UNDANG NOMOR 17 TAHUN 2014 - Alfaridah, Dini Inasyah; Alfarijah, Dina Aisyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the ineffectiveness of the authority of the Judicial Commission in proposing the appointment of supreme court justices due to the practice of the House of Representatives of the Republic of Indonesia which is still conducting a fit and proper test, even though the Constitutional Court Decision Number 27/PUU-XI/2013 has limited the authority of the House of Representatives of the Republic of Indonesia to give approval. This has led to politicization in the process of appointing supreme court justices which has the potential to disrupt the independence of the judiciary. The purpose of this study is to analyze the mechanism of consideration of the House of Representatives in giving approval to candidates for supreme court justices, the existence of the Judicial Commission in proposing supreme court justices, and the effectiveness of the implementation of the authority of the Judicial Commission in relation to Article 71 of Law Number 17 of 2014. The research method uses a qualitative approach with a normative juridical method. Data was collected through literature studies and interviews, then analyzed descriptively analytically. The results of the study show that: (1) the consideration mechanism of the House of Representatives of the Republic of Indonesia still refers to old provisions that are contrary to the Constitutional Court's decision; (2) the existence of the Judicial Commission can be strengthened through the implementation of the Constitutional Court's decision No. 27/PUU-XI/2013; (3) the effectiveness of the implementation of the authority of the Judicial Commission is considered ineffective because Article 71 of the MD3 Law in practice still opens up room for political intervention. It is necessary to improve regulations and strengthen the authority of the Judicial Commission to realize the appointment of independent and qualified supreme court judges.